New approaches to antimalarial chemotherapy: design and synthesis of bicyclic endoperoxides and of peptide and peptidomimetic carbonyl containing cysteine protease inhibitors - Verissimo, Edite (2011)
Tese dout., Química Orgânica, Universidade do Algarve, 2007